Harmonization of Various Institutions in Preventing and Overcoming the Impact of Child Marriage - Muhamad Hasan Sebyar; Tauhid Tauhid; Fauzul Fil Amri (Faculty of Law, Universitas Pekalongan, 2023)
Marriage dispensation is an alternative to resolve the issue of marriage at the age of under 19 years. However, the decision to grant marriage dispensation may have a negative impact on household harmony, eventually resulting in divorce. To overcome this issue, judges are authorized to reduce the adverse effects of under-aged marriage. This study aimed to identify and analyze the harmonization between the Panyabungan Religious Court and other institutions in preventing and reducing the impact of child marriage dispensation. This research employed the legal and the socio-legal approaches. The legal approach was used to analyze the marriage dispensation decision at the Panyabungan Religious Court, while the socio-legal approach was used to analyze the social interactions that occurred between the Religious Court and other institutions. The results of this study indicated that the harmonization between the Panyabungan Religious Court and other institutions with common functions and purposes in the prevention and mitigation the impact of child marriage dispensation is considered to be good. Collaboration was already in motion between the Customary Institution and KUA (the Office of Religious Affairs) or the Ministry of Religious Affairs. Further collaboration with the Health Office, Education Office, Manpower Office, Women's Empowerment and Child Protection Office, Family Planning Office, and MUI (Indonesian Ulama Council) of Mandailing Natal Regency needs to be explored in the future. It is hoped that this cooperation will occur not only in the Panyabungan Religious Court but in all the Religious Courts throughout Indonesia.